Pengaruh Pelatihan Profesional, Penghargaan Finansial, dan Pertimbangan Pasar Kerja terhadap Minat Berkarir Akuntan Publik - Anita Norlaela; Muslimin Muslimin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
The number of public accountants in Indonesia is still relatively minimal, because accounting graduates have less interest in a career as public accountants. There are many factors that influence accounting graduates in choosing a career, including financial factors, training, and the job market. The purpose of this study was to examine and analyze the effect of professional training, financial rewards, and labor market considerations on public accountant career interests. The population in this study were Accounting S1 students from UPN "Veteran" East Java and Airlangga University class of 2018 and 2019. The research method used quantitative research. The sampling technique used purposive sampling method, while for determining the number of samples using the Slovin formula with a total of 91 respondents. Data collection techniques used in this study using a questionnaire. The collected data were analyzed using Partial Least Square (PLS) analysis technique with SmartPLS 3.0 software. The results of this study indicate that: (1) Professional Training has a positive and significant effect on Public Accountant Career Interests. (2) Financial Award has no significant effect on Public Accountant Career Interest. (3) Labor market considerations have a positive and significant impact on the Career Interest of a Public Accountant. Keywords: Professional Training; Financial Awards; Labor Market Considerations; Public Accountant Career Interest.